Modellentwicklung eines ganzheitlichen Projektmanagementsystems für kerntechnische Rückbauprojekte (MogaMaR) : Schlussbericht des Forschungsvorhabens - Hübner, FelixVolk, RebekkaSecer, OktayKühn, DanielSahre, PeterKnappik, ReinhardSchultmann, FrankGentes, SaschaBoth, Petra von (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2018)
The development of a holistic and integrated project management and planning system is crucial to avoid deviations from the plan and to consider uncertainties in the planning stage of nuclear dismantling projects. Therefore, in the research project MogaMaR characteristics of such projects as well as shortcomings in the current project management were identified. On the basis of these findings, a holistic project management system for nuclear dismantling projects was developed.